2008
DOI: 10.1038/ejhg.2008.165
|View full text |Cite
|
Sign up to set email alerts
|

Prader–Willi syndrome

Abstract: In association withPrader-Willi syndrome Prader -Willi syndrome (PWS) is a highly variable genetic disorder affecting multiple body systems whose most consistent major manifestations include hypotonia with poor suck and poor weight gain in infancy; mild mental retardation, hypogonadism, growth hormone insufficiency causing short stature for the family, early childhood-onset hyperphagia and obesity, characteristic appearance, and behavioral and sometimes psychiatric disturbance. Many more minor characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
487
0
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(506 citation statements)
references
References 69 publications
7
487
0
12
Order By: Relevance
“…Infants with PWS demonstrate dramatically reduced nursing and crying, with high rates of hypotonia and hypersomnolence (Cassidy & Driscoll, 2008;Holm et al, 1993;Peters, 2014), supporting this prediction. Here, we ask if comparable effects are present in a domain not previously tested in PWS but potentially relevant to parental investment: music.…”
Section: Genomic Imprinting Is Implicated In the Psychology Of Musicsupporting
confidence: 60%
“…Infants with PWS demonstrate dramatically reduced nursing and crying, with high rates of hypotonia and hypersomnolence (Cassidy & Driscoll, 2008;Holm et al, 1993;Peters, 2014), supporting this prediction. Here, we ask if comparable effects are present in a domain not previously tested in PWS but potentially relevant to parental investment: music.…”
Section: Genomic Imprinting Is Implicated In the Psychology Of Musicsupporting
confidence: 60%
“…Published data on thyroid and adrenal function are limited. In most reports, thyroid and adrenal function are reported to be normal, although secondary hypothyroidism has been described [2,10,23,25,26,27,28]. Remarkably, in a recent study central adrenal insufficiency was demonstrated in 60% of the PWS children [29].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of this 4th group would have clearly distinguished whether the differences seen in these youngsters with PWS might be related to GHRT or perhaps to other management factors such as diet or physical activity [5,12]. Nonetheless, this study shows novel data in children with PWS having lower BMC and BMD in the hips compared to obese counterparts but similar to lean controls.…”
Section: Discussionmentioning
confidence: 62%
“…Overall, individuals with PWS present a low lean mass and a relatively high body fat content [5]. Adults with PWS not on GH (especially males) display high fat mass in the legs [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation